Dilemmas of modelling and decision-making in environmental research. (January 2018) - Allison, Andrew E.F.; Dickson, Mark E.; Fisher, Karen T.; Thrush, Simon F.
Abstract: Multiple dilemmas confound social-ecological modelling. This review paper focuses on two: a modeller's dilemma associated with determining appropriate levels of model simplification, and a dilemma of decision-making relating to the use of models that were never designed to predict. We analyse approaches for addressing these dilemmas as they relate to shallow coastal systems and conclude that wicked problems cannot be adequately addressed using traditional disciplinary or systems engineering modelling. Simplified inter- and trans-disciplinary models have the potential to identify directions of system change, challenge thinking in disciplinary silos, and ultimately confront the dilemmas of social-ecological modelling. Highlights: Critical analysis of two dilemmas that confound social-ecological modelling. Wicked problems cannot be adequately addressed in disciplinary silos. Simple inter- and transdisciplinary models can confront the two dilemmas.